2016
DOI: 10.2355/isijinternational.isijint-2015-417
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Model for Limestone Decomposition under BOF Steelmaking Condition

Abstract: In BOF steelmaking process, high-activity lime has been widely used to form an appropriate slag as a medium for the removal of non-volatile impurities from the hot metal treated. In recent years, however, great attention has been paid to the possibility of directly using limestone instead of lime in the furnace. Despite laboratory experiments and industrial trials have proven the feasibility of the technique, a list of underlying issues still require more considerations, e.g., thermodynamics and kinetics of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In recent years, the application of limestone instead of lime for slagging has attracted a lot of attentions [16][17][18]. The formed CO 2 gas by limestone decomposition can destroy the dicalcium silicate reaction layer at the slag/lime interface, thus, which can speed up the mass transfer of lime dissolution during limestone slagging mode [18].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the application of limestone instead of lime for slagging has attracted a lot of attentions [16][17][18]. The formed CO 2 gas by limestone decomposition can destroy the dicalcium silicate reaction layer at the slag/lime interface, thus, which can speed up the mass transfer of lime dissolution during limestone slagging mode [18].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the conventional lime steelmaking process, the dissolution of limestone is accompanied by the decomposition reaction of limestone in the limestone steelmaking process. The decomposition of limestone in converter slag is a strong endothermic reaction which has been studied by many researchers [13][14][15]. Deng et al [16] studied the dissolution of limestone in slag at 1600°C and concluded that the structure of the decomposed limestone became very dense at the boundary, resulting in a dense CaO layer at the surface of the generated lime.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the conventional lime steelmaking process, the dissolution of limestone is accompanied by the decomposition reaction of limestone in the limestone steelmaking process. The decomposition of limestone in converter slag is a strong endothermic reaction which has been studied by many researchers [1315]. Deng et al.…”
Section: Introductionmentioning
confidence: 99%